The Ideal of Imperial Citizenship 1895-1919 - Gorman, Patrick Daniel (My University, 2002)
As all early twentieth century British schoolchildren knew, Great Britain presided over an Empire upon which the sun never set. Yet the Empire itself was not a unified state, the solid red on imperial maps belying the dizzying array of political identities which existed under the Union Jack. Some Britons believed this diversity spoke to the legitimacy of the nation's imperial rule, and saw Empire as a vehicle of peace and progress. Others feared the loss of an Anglo-European cultural identity, and sought to reassert British values at the expense of indigenous local identities. Adherents of each view saw in the idea and institution of citizenship the maens through which to pursue their goals.
This dissertation examines efforts amongst British conservatives in the early twentieth century to develop a concept of imperial citizenship which would both unite the Crown's multitudinous subjects and cement Britain's political power on the world stage. Through a discussion of the ideas and careers of five select imperialists- Lionel Curtis, John Buchan, Richard Jebb, Arnold White, and Thomas Sedgwick- it is demonstrated that ideas of imperial citizenship were contested between conservatives who developed a gradually inclusive view of Empire and those who held to a more inclusive, Anglo-centric understanding of Empire. Specific attention is given to the issue of intra-imperial immigration as an arena where the debate concerning imperial citizenship was starkly and decisively apparent. The difficulties encountered by British conservatives in articulating a cohesive concept of imperial citizenship, the dissertation concludes, resulted from two main factors: their failure to effectively incorporate colonial nationalism into their prescriptions, and their inability to create practical means by which a truly pan-imperial citizenship could flourish.
Keywords: History; History